(untitled) (European Journal of Health Research, 2019)
The European Higher Education Area is especially concerned with the way teaching is performed at graduate and postgraduate levels. It is a matter or research with a special interest in areas such as those that belong to Health Sciences disciplines. How the students learn is related to the strategies they use to approach to the contents to be assimilated. The goal of this study is to know students’ perception and learning approaches in occupational medicine modules. Students enrolled in an occupational medicine module of active learning filled the Course Experience Questionnaire (CEQ) and the Study Process Questionnaire (R-SPQ-2F). Workload perception and learning approaches and their relationship were analyzed. Students showed consistent appropriateness scores and showed a significantly higher deep than surface approach (R-SPQ-2F) with a relationship between both. The findings support that with active learning procedures, there is an appropriateness in workload perception and students’ deep approach. To ameliorate teaching tools it is suggested to implement research assessment systems to check adequacy of active learning systems.